Chemotherapy-Induced Constipation and Diarrhea: Pathophysiology, Current and Emerging Treatments - McQuade, Rachel M.; Stojanovska, Vanesa; Abalo, Raquel; Bornstein, Joel C.; Nurgali, Kulmira (Frontiers in Pharmacology, 2016)
Gastrointestinal (GI) side-effects of chemotherapy are a debilitating and often overlooked clinical hurdle in cancer management. Chemotherapy-induced constipation (CIC) and diarrhoea (CID) present a constant challenge in the efficient and tolerable treatment of cancer and are amongst the primary contributors to dose reductions, delays and cessation of treatment. Although prevalence of CIC is hard to estimate, it is believed to affect approximately 16% of cancer patients, whilst incidence of CID has been estimated to be as high as 80%. Despite this, the underlying mechanisms of both CID and CIC remain unclear, but are believed to result from a combination of intersecting mechanisms including inflammation, secretory dysfunctions, GI dysmotility and alterations in GI innervation. Current treatments for CIC and CID aim to reduce the severity of symptoms rather than combating the pathophysiological mechanisms of dysfunction, and often result in worsening of already chronic GI symptoms or trigger the onset of a plethora of other side-effects including respiratory depression, uneven heartbeat, seizures and neurotoxicity. Emerging treatments including those targeting the enteric nervous system present promising avenues to alleviate CID and CIC. Identification of potential targets for novel therapies to alleviate chemotherapy-induced toxicity is essential to improve clinical outcomes and quality of life amongst cancer sufferers.